COMPARISON BETWEEN PANRETINAL PHOTOCOAGULATION AND PANRETINAL PHOTOCOAGULATION PLUS INTRAVITREAL BEVACIZUMAB IN PROLIFERATIVE DIABETIC RETINOPATHY - Ahmad, Mushtaq; Jan, Sanaullah (Journal of Ayub Medical College Abbottabad, 2012)
Background: Patients with diabetes often develop ocular complications. The most common and most blinding of these complications, however, is diabetic retinopathy. The objective of this study was to compare the retinal neovessels regression in Proliferative Diabetic Retinopathy (PDR) treated with Pan Retinal Photocoagulation (PRP) versus panretinal photocoagulation plus Intra Vitreal Bevacizumab (IVB). Methods: A comparative study was conducted at Khyber Institute of Ophthalmic Medical Sciences, Hayatabad Medical Complex, Peshawar from 1st October 2010 to 31st August 2011. A total of 54 eyes were randomised into two groups. Neovessels status was assessed before and at every follow up visit. Neo Vessels on the Disc (NVDs) were assessed as per percentage of NVD occupying the disc surface whereas Neo Vessels Elsewhere (NVE) were also assessed as per reference to disc surface diameter. Results: Neovascularization on the disc was 40±5% at presentation which increased to 50±7% on 30th day and stabilised to 40±6% on day 90 in PRP group. In PRP-plus group, 40±7% NVD regressed to 10±5% on 30th day and 11±3% on day 90. The NVE in PRP group was 2±0.75% at baseline, 2.25±0.75% on 30th day, and 2.00±0.50% on day 90. In PRP-plus group it was 2±0.50% at baseline, 1±0.5% on day 30, and 0.75±0.25% on day 90. On day 90 both the groups had highly significant different NVD (p=0.00008) and NVE (p=0.0001). Conclusion: Intra Vitreal Bevacizumab in short term is effective as adjunctive treatment to PRP with early and higher rate of retinal neovessels regression than PRP alone in PDR patients. Keywords: Panretinal Photocoagulation, Diabetic Retinopathy, Intravitreal Bevacizumab